ANALYSIS OF SEVEN CASES OF ANGULAR CHEILITIS IN CHILDREN WITH BODY MASS INDEX AND BLOOD TEST RESULTS - Abu Bakar (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: Angular cheilitis is an acute or chronic inflammation at the angular of the lip which is characterized with fissures and the cracks. Objectives: The aim of this paper was to analyze seven cases of angular cheilitis in children with body mass index and blood test results. Case:  There were seven children patients taken by their parents came to Baiturrahmah Academic Dental Hospital with a same complaint on a day. They complained about the injury and pain while open the mouth in the angular of the mouth. Intra oral examination showed the different clinical appearance at the angular of the mouth (white or red lesions and fissured or cracked). Body mass index analysis showed all the patients are underweight (9 -14) and mostly of the patients have a hemoglobin less than normal. Case Management: Pharmacological management was prescribed multivitamin supplements (vitamin B complex in syrup) and prescribed nystatin topically. One week after first visit, the anglar chelitis lesions has healed Conclusion: Low BMI might be the predisposing factor of the diseases. Keywords: Angular Cheilitis, Blood test,  Body mass index